Developing climate-resilient, direct-seeded, adapted multiple-stress-tolerant rice applying genomics-assisted breeding - Sandhu, Nitika; Yadav, Shailesh; Catolos, Margaret; Cruz, Ma Teresa Sta; Kumar, Arvind (Frontiers Media, 2021)
There is an urgent need to breed dry direct-seeded adapted rice varieties in order to address the emerging scenario of water–labor shortage. The aim of this study was to develop high-yielding, direct-seeded adapted varieties utilizing biparental to multiparental crosses involving as many as six different parents in conventional breeding programs and 12 parents in genomics-assisted breeding programs. The rigorous single plant selections were followed from the F2 generation onwards utilizing phenotypic selection and quantitative trait locus (QTL)/gene-based/linked markers for tracking the presence of desirable alleles of targeted QTL/genes. In conventional breeding, multiparent lines had significantly higher yields (2,072–6,569 kg ha−1) than the biparental lines (1,493–6,326 kg ha−1). GAB lines derived from multiparent crosses had significantly higher (3,293–6,719 kg ha−1) yields than the multiparent lines from conventional breeding (2,072–6,569 kg ha−1). Eleven promising lines from genomics-assisted breeding carrying 7–11 QTL/genes and eight lines from conventional breeding with grain-yield improvement from 727 to 1,705 kg ha−1 and 68 to 902 kg ha−1, respectively, over the best check were selected. The developed lines may be released as varieties/parental lines to develop better rice varieties for direct-seeded situations or as novel breeding material to study genetic interactions.